2021
DOI: 10.3390/ani11040933
|View full text |Cite
|
Sign up to set email alerts
|

Horse Preferences for Insolation, Shade or Mist Curtain in the Paddock under Heat Conditions: Cardiac and Behavioural Response Analysis

Abstract: The horse’s welfare and, consequently, the emotional arousal may be connected with stressful environmental conditions. This study aimed to determine whether horses show behavioural or physiological symptoms of thermal discomfort and if their behaviour and cardiac parameters are related to freely chosen insolated (IS), shaded (SH), or water sprayed (with a mist curtain (MC)) areas in a paddock under heat conditions (29–32 °C, 42.0 ± 1.5% humidity). Twelve adult horses freely moving in the paddock were studied d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…However, it was not observed that the horses expected the sound signal that they had heard on the previous day of the experiment. Varied behaviour of the horses during their stay in the paddock was also noted by Janczarek et al [ 24 ]. As Morris [ 25 ] points out, one of the reasons for this variation is the mood of the animals which may change on a daily basis.…”
Section: Discussionsupporting
confidence: 60%
“…However, it was not observed that the horses expected the sound signal that they had heard on the previous day of the experiment. Varied behaviour of the horses during their stay in the paddock was also noted by Janczarek et al [ 24 ]. As Morris [ 25 ] points out, one of the reasons for this variation is the mood of the animals which may change on a daily basis.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, Bilgili et al [ 24 ], reported that cutaneous and respiratory evaporative heat loss contributed approximately 90% and 10%, respectively, to total evaporative heat loss in humans. These two studies, as well as others [ 7 , 8 ], demonstrate that horses and humans have comparable thermal regulation. Due to the similarities in thermal regulation between horses and humans, the ice vest could be used to provide heat protection for horses.…”
Section: Introductionsupporting
confidence: 65%
“…Heat stress due to either climate or exercise, or both, has been shown to increase the risk of heat stroke in horses [ 6 ]. Horses have a high metabolic rate but a small surface area for heat dissipation, as described by Janczarek et al [ 7 ]. As a result, horses must be actively cooled, even more so in hot environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations